The development of a mobile learning application to aid ECG interpretations among first- and second-year medical students - Justin Zumwalt; Ashley Keener (Discover Education)
Abstract The first two years of undergraduate medical education include foundational science and clinical training such as accurately interpreting electrocardiograms (ECGs). ECG education is traditionally delivered via lecture-based presentations in a formal classroom setting. However, students are increasingly finding mobile apps to be instructive to use in a non-formal setting outside of the classroom. This report describes the development of a mobile app to aid with ECG interpretations. Quantitative data included the frequency to which medical students used the app. Findings reveal the app was accessed the most frequently when first launched and students may be most interested in learning about certain arrhythmias more than others, potentially ones they found more difficult to learn.